Biochemical Evaluation, Anthropometric Measurements in Assessment of Microvascular Complications in Females with Type-2 Diabetes Mellitus - Munilakshmi, U; Shashidhar, KN; Harish, R; Reddy, Madhavi; Lakshmaiah, V (Asian Journal of Medical Sciences, 2013)
Objective: To investigate the role of the biochemical parameters in the prediction of the microvascular complications in Type 2 diabetes and non-diabetes female patients. Materials and Methods: The present study was conducted in R L Jalappa hospital attended to Sri Devearj Urs Medical College, Kolar. Randomly selected 45 female type 2 diabetes and non diabetes patients with the age group of 45-55 years attending medicine outpatient department from March 2011 to January 2012 were included in the study. Anthropometric and biochemical parameters were analyzed by standard methods. Results: Among variables studied height, obesity index and diastolic blood pressure (DBP) were statistically significant between diabetes and non-diabetes. Diabetic female subjects showed higher values for insulin (16.90mcU/ml), uric acid (4.36mg/dl), urine albumin (305.71mg/dl) and albumin creatinine ratio (13.18mg/g) when compared with non-diabetic female subjects. The mean values for total cholesterol (182.09mg/dl), triglycerides (209.04mg/dl), high density lipoproteins (HDL-c) (36.44mg/dl), low density lipoproteins (LDL-c) (100.09mg/dl), Non-HDL (145.64mg/dl) and eGFR (97.03) in diabetes females and in non diabetes females 187.69mg/dl, 143.78mg/dl and 43.46mg/dl,115.20mg/dl, 144.22mg/dl, 87.03 for TC, triglycerides, HDL, LDL, non-HDL and eGFR respectively. Among parameters evaluated triglycerides and LDL-c were significant between diabetic and nondiabetic female subjects. Conclusion: In this study we observed 26.6% of nephropathy, 13.3% of retinopathy and 6.6% of neuropathy in diabetes females. However non-diabetes female subjects showed higher significant TC and LDL-c levels. This suggests that above the age of 45 year females requires comprehensive evaluation of anthropometric and biochemical parameters to avoid micro and macro vascular complications. DOI: http://dx.doi.org/10.3126/ajms.v5i2.8651 Asian Journal of Medical Science, Volume-5(2) 2014: 113-119